Disease management at the wildlife‐livestock interface: Using whole‐genome sequencing to study the role of elk in Mycobacterium bovis transmission in Michigan, USA. Issue 9 (10th May 2019) - Salvador, Liliana C. M.; O'Brien, Daniel J.; Cosgrove, Melinda K.; Stuber, Tod P.; Schooley, Angie M.; Crispell, Joseph; Church, Steven V.; Gröhn, Yrjö T.; Robbe‐Austerman, Suelee; Kao, Rowland R.
Abstract: The role of wildlife in the persistence and spread of livestock diseases is difficult to quantify and control. These difficulties are exacerbated when several wildlife species are potentially involved. Bovine tuberculosis (bTB), caused by Mycobacterium bovis, has experienced an ecological shift in Michigan, with spillover from cattle leading to an endemically infected white‐tailed deer (deer) population. It has potentially substantial implications for the health and well‐being of both wildlife and livestock and incurs a significant economic cost to industry and government. Deer are known to act as a reservoir of infection, with evidence of M. bovis transmission to sympatric elk and cattle populations. However, the role of elk in the circulation of M. bovis is uncertain; they are few in number, but range further than deer, so may enable long distance spread. Combining Whole Genome Sequences (WGS) for M. bovis isolates from exceptionally well‐observed populations of elk, deer and cattle with spatiotemporal locations, we use spatial and Bayesian phylogenetic analyses to show strong spatiotemporal admixture of M. bovis isolates. Clustering of bTB in elk and cattle suggests either intraspecies transmission within the two populations, or exposure to a common source. However, there is no support for significant pathogen transfer amongst elk and cattle, and our data are in accordance with existing evidence that interspecies transmission in Michigan is likely only maintained by deer. This study demonstrates the value of whole genome population studies of M. bovis transmission at the wildlife‐livestock interface, providing insights into bTB management in an endemic system.